The Supreme Court reborn : the constitutional revolution in the age of Roosevelt - Leuchtenburg, William E. (William Edward), 1922-2025 (Oxford University Press, 1996)
For almost sixty years, the results of the New Deal have been an accepted part of political life. Social Security, to take one example, is now seen as every American's birthright. But to validate this revolutionary legislation, Franklin Roosevelt had to fight a ferocious battle against the opposition of the Supreme Court--which was entrenched in laissez faire orthodoxy. After many lost battles, Roosevelt won his war with the Court, launching a Constitutional revolution that went far beyond anything he envisioned. In The Supreme Court Reborn, esteemed scholar William E. Leuchtenburg explores th.